How Physicians Support Mothers of Children with Duchenne Muscular Dystrophy. (September 2015) - Fujino, Haruo; Saito, Toshio; Matsumura, Tsuyoshi; Shibata, Saki; Iwata, Yuko; Fujimura, Harutoshi; Shinno, Susumu; Imura, Osamu
Communicating about Duchenne muscular dystrophy and its prognosis can be difficult for affected children and their family. We focused on how physicians provide support to the mothers of children with Duchenne muscular dystrophy who have difficulty communicating about the condition with their child. The eligible participants were certified child neurologists of the Japanese Society of Child Neurology. Participants responded to questionnaires consisting of free descriptions of a vignette of a child with Duchenne muscular dystrophy and a mother. We analyzed 263 responses of the participants. We found 4 themes on advising mothers, involving encouraging communication, family autonomy, supporting family, and considering the child's concerns. These results provide a better understanding of the communication between physicians and family members who need help sharing information with a child with Duchenne muscular dystrophy. These findings will assist clinical practitioners in supporting families and the affected children throughout the course of their illness.